Poverty Reduction Policies and Practices in Developing Asia - Almas Heshmati; Esfandiar Maasoumi; Guanghua Wan (Springer Singapore, 2015)
This book looks at the major policy challenges facing developing Asia and how the region sustains rapid economic growth to reduce multidimensional poverty through socially inclusive and environmentally sustainable measures. Asia is facing many challenges arising from population growth, rapid urbanization, provision of services, climate change and the need to redress declining growth after the global financial crisis. This book examines poverty and related issues and aims to advance the development of new tools and measurement of multidimensional poverty and poverty reduction policy analysis. The book covers a wide range of issues, including determinants and causes of poverty and its changes; consequences and impacts of poverty on human capital formation, growth and consumption; assessment of poverty strategies and policies; the role of government, NGOs and other institutions in poverty reduction; rural-urban migration and poverty; vulnerability to poverty; breakdown of poverty into chronic and transitory components; and a comparative study on poverty issues in Asia and other regions. The book will appeal to all those interested in economic development, resources, policies and economic welfare and growth.
Keywords: 330; Armutsbekämpfung; Mikrofinanzierung; Städtische Armut; Ländliche Armut; Asien; Asiatisch-pazifischer Raum